Care of frail and older adults: A content analysis of paramedic operational clinical practice guidelines. (May 2021) - Harris, Wayne; Stirling, Christine; Williams, Anne-Marie; Lucas, Peter
Highlights: Older adults are underrepresented in paramedic clinical practice guidelines (CPGs). Age descriptors were inconsistently applied within the CPGs. Diverse drug dosing schedules were evident across CPGs. Development of evidence-based older adult specific CPGs may increase patient safety. Abstract: Introduction: Frailty rates are increasing with population ageing. In paramedicine, Clinical Practice Guidelines (CPGs) are essential documents that support decision making, yet little evidence exists regarding the support CPGs provide paramedics in the care of frail and older adults. Aim: To investigate how CPGs support paramedics' care of frail and older adults. Methods: CPGs from nine Australasian paramedic services were collected in 2019. Content analysis was used to explore two hundred and thirty-seven individual CPGs for decision support information regarding frail and older adults. Results: Evidence-based content relating to older adults was sparse compared to paediatric content. Two overarching decision support domains were identified, patient assessment and management. Inconsistent age descriptors were widespread, particularly in pharmacological guidelines. Five service providers' CPGs contained validated assessment instruments for use with older adults. Conclusion: Decision support documentation regarding frail and older adults varies across Australasian paramedic services. Frailty and older adult specific CPGs, and validated assessment instruments suitable to the paramedicine environment could improve paramedic decision making and minimise patient risk. A collaborative approach encompassing service providers and educational institutions is crucial to develop consistent, evidence-based CPGs relevant to older adults.